2016
DOI: 10.1002/prep.201600003
|View full text |Cite
|
Sign up to set email alerts
|

Structural Defect Evolution of TATB‐Based Compounds Induced by Processing Operations and Thermal Treatments

Abstract: 1IntroductionSolid explosives displays trongly heterogeneous microstructures, which are known to evolveu nderp rocessing, thermal treatments, and mechanical loads. In turn, microstructure evolutions may affect macroscopic properties, such as shock and impact sensitivity,o rt hermo-mechanicalb ehavior.T herefore, it is of crucial importancet oc haracterizee xplosives microstructures and their evolutions. The subject can still be considered to be in its infancy,b ut has grown significantly in recent years.G iven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Unlabeled TATB (blue) exhibits the typical PXRD pattern for production level TATB [27,[38][39][40]. The (0 0 2) reflectance dominates the pattern at ~30°2Θ.…”
Section: Powder X-ray Characterizationmentioning
confidence: 99%
“…Unlabeled TATB (blue) exhibits the typical PXRD pattern for production level TATB [27,[38][39][40]. The (0 0 2) reflectance dominates the pattern at ~30°2Θ.…”
Section: Powder X-ray Characterizationmentioning
confidence: 99%
“…With advancing detection technologies such as optical microscopy (OM), scanning electron microscopy (SEM), neutron diffraction (NRD), small-angle neutron scattering (SANS), and small-angle X-ray scattering (SAXS), it is possible to study the multiphase interfaces, TATB crystals, binders, and holes inside PBX in complex environments, as well as the distribution characterization of molding powder and porosity testing, to gradually obtain a large amount of microstructure information of pressed TATB PBXs. Watkins, Tang, and others [7,19,[24][25][26][27][28][29][30][31][32] studied the crystal orientation, crystal fragmentation, porosity, and binder behavior during the expansion process of PBX pressed under different conditions. They demonstrated that the temperature is an important pressing parameter during PBX pressing, because high temperatures improve the flowability of polymer binders, leading to better bonding with explosive particles and reducing cracks and fragmentation in the explosive.…”
Section: Introductionmentioning
confidence: 99%
“…An accurate model that allows the calculation of a joint parameter distribution is necessary to understand fully the quantitative capability of XRD in determining crystallite size. However, for certain samples of consistent crystallite shape measured equivalently, it has been shown that these methods are useful for the determination of crystal strain, for example in tracking the evolution of single samples subjected to stress (Brown et al, 2014;Zotov et al, 2017), or to compare the effects of processing on the properties of materials (Scorticati et al, 2015;Schimpf et al, 2013;Leineweber, 2011;Guerain et al, 2016). For these ideal samples, XRD methods are preferred over image-based techniques for relatively high throughput crystallographic size information and are uniquely able to provide certain data such as lattice strain.…”
Section: Introductionmentioning
confidence: 99%